Pengembangan Media Diorama Koca (Kotak Kaca) Materi Perubahan Cuaca Kualitas Media Kelas III - Basir, Latifah Nur; Asmarani, Ratih; Faizi, Ahmad (Prodi Pendidikan Guru Sekolah Dasar, 2024)
Learning as a strategy for continuing education. Where the learning objectives of each subject and class stage in elementary schools require different learning resources. In current developments, teachers must be able to access the latest technology so that students can easily understand the material. Therefore it is very important to have media so that it can make students master the material and be enthusiastic about the length of the learning process. The purpose of this study was to develop teaching materials for koca diorama (Kotak Kaca) for third-grade students in elementary schools. To improve students' understanding of class III Basic Science Concepts, this study also aims to understand the quality of the Koca diorama media (Kotak Kaca) used in Weather Change material. By using the ADDIE paradigm which develops systematically. With the modified ADDIE model, the needs of the participants are met through the stages of analysis, design, development, implementation, and evaluation. In this study, the research subjects were grade 3 students in the 2022–2023 academic year. By using a questionnaire sheet validation technique, media data validation, and material data validation to determine quality using the proportion of validation results. The quality of media for education has a value of 94.1% with a very valid category and can be used without improvement. From this, it can be concluded that the widely used educational materials meet high standards of validity and can be used without improvement.